ChemInform Abstract: One‐Pot Multi‐Component Synthesis and Solid State Structures of Functionally Rich Polyether Macrocycles. Issue 15 (15th April 2014) - Vishe, Mahesh; Hrdina, Radim; Guenee, Laure; Besnard, Celine; Lacour, Jerome
Abstract Rhodium‐catalyzed decomposition of methyl diazoacetoacetate in the presence of substituted cyclic ethers results in the formation of novel functionalized macrocycles.